Doctoral and master’s supervision: Does preference for research versus teaching really make a difference? - Callaghan, C.W. (South African Journal of Higher Education, 2018)
Longstanding debates exist across literatures as to potential consequences of preferences for teaching versus research for a host of academic work outcomes. Seemingly absent from the literature, however, is evidence of the effect of such preferences on academic outputs, such as master’s and doctoral supervisions, and the extent these preferences and their effects are gendered. Applying a comprehensive purposive sampling strategy, a large South African higher institution was sampled. Structural equation models were used, with tests of path invariance to test for gender moderation, as well as further tests of such preferences as mediators of relationships between certain academic productivity variables (research publications output, academic experience, preference for quantitative versus qualitative research methods, and family-work spiller effects), and master’s or doctoral supervisions. Findings suggest that men with an oppositional preference for teaching (research) report significantly higher (lower) numbers of successful master’s supervisions. No difference in master’s supervisions was found by gender, but men were found to have significantly higher numbers of doctoral supervisions. Dependent children are found to be associated with more master’s degree supervisions, but only for male academics. However, total publications output is more strongly associated with master’s supervision for female academics. Academic experience is significantly associated with numbers of doctoral supervisions only for male academics. Implications of these findings are discussed, and recommendations are made.